Transmission system for biomedical signals through the general packet radio service GPRS (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
The access to health systems in Colombia for remote towns, is a difficulty that has motivated great efforts in finding solutions in telemedicine to shorten the distances through the use of communication systems between different cities. The apparent growth of cellular communications coverage in the country has prompted its use in various processes of telemedicine. This paper presents the results obtained in the process of design, implementation and validation of a platform for capturing, processing and transmission of biomedical signals, using the General Packet Radio Service GPRS, which can be accessed remotely through a graphical front end to manage information obtained from a cloud server. We evaluate the system by measuring the precision of the acquired biomedical signals (above 98,5%); the time of connection to the cellular network (2,45 seconds) and the transmission rate subject to the conditions for provision of GSM service on two different protocols (1,23 seconds 5Kb files UDP). Finally, the ECG signal was compressed for transmission using the ARX model.
Keywords: Biomedical Signals; GPRS; Telemedicine; Transmission